2021
DOI: 10.1145/3479858
|View full text |Cite
|
Sign up to set email alerts
|

Child Safety in the Smart Home: Parents' Perceptions, Needs, and Mitigation Strategies

Abstract: Concerns about child physical and digital safety are emerging with families' adoption of smart home technologies such as robot vacuums and smart speakers. To better understand parents' definitions and perceptions of child safety regarding smart home technologies, we interviewed 23 parents who are smart home adopters. We contribute insights into parents' perceptions of the physical and digital safety risks smart home technologies pose to children, and how such perceptions formed and changed across three phases.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 102 publications
(65 reference statements)
0
9
1
Order By: Relevance
“…In contrast, Prasad et al [149] (interview, 𝑛 = 20) considered parental privacy concerns towards service providers and manufacturers and how they affect their children. Sun et al [171] (interview, 𝑛 = 23) identified six factors which, according to them, influence parents' perception of privacy risks, including parenting style, tech-savviness, trust in manufacturer, age of the children, features of the used devices and news media reporting.…”
Section: Periodmentioning
confidence: 99%
“…In contrast, Prasad et al [149] (interview, 𝑛 = 20) considered parental privacy concerns towards service providers and manufacturers and how they affect their children. Sun et al [171] (interview, 𝑛 = 23) identified six factors which, according to them, influence parents' perception of privacy risks, including parenting style, tech-savviness, trust in manufacturer, age of the children, features of the used devices and news media reporting.…”
Section: Periodmentioning
confidence: 99%
“…The study indicates a considerable lack of awareness among parents regarding cybersecurity threats that children face online. Sun et al (2021) conduct a study by interviewing 23 parents who live in smart homes across Canada and the USA via Zoom video calls. They show that parents’ perceptions and mitigation strategies regarding their children’s safety in smart homes encompassed physical and digital aspects.…”
Section: Background and Related Workmentioning
confidence: 99%
“…These differences influence their ways of using smart home devices, which could cause power imbalances between household members (Geeng et al, 2019;Van der Zeeuw et al, 2020;Zeng et al, 2017). To study these dynamics between household members, it could furthermore be of interest to study the digital skills of children and adolescents as they often are not considered enough as individuals with unique skills and needs (Sun et al, 2021).…”
Section: Limitations and Future Researchmentioning
confidence: 99%